If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = -7 + 2x Reorder the terms: 7 + 3x = -7 + 2x Solving 7 + 3x = -7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + 3x + -2x = -7 + 2x + -2x Combine like terms: 3x + -2x = 1x 7 + 1x = -7 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + 1x = -7 + 0 7 + 1x = -7 Add '-7' to each side of the equation. 7 + -7 + 1x = -7 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = -7 + -7 1x = -7 + -7 Combine like terms: -7 + -7 = -14 1x = -14 Divide each side by '1'. x = -14 Simplifying x = -14
| 21=n+21 | | 5x+3x=7x+2x | | 5/6n=10 | | -16n=48 | | 170/33 | | N+17=6 | | 9x^2-4x-10=x-8 | | 15e=-45 | | 3/7n=-18 | | 3/7n=-19 | | (e+3)*4=24 | | -3x^2+5y^2+7z^2=0 | | 3x^2-5y^2+7z^2=0 | | 6k=-12 | | 4.2x=-8.4 | | -3/8n=9 | | 3.9x-5.8+7x=7.9x-16.3 | | 5/6n=-25 | | sqrt(17k^2+16k)=0 | | 2x-8=3x-16 | | 18x^2-12x-12=0 | | 6(x+5)-(4x-7)= | | 19/5x−1/3=4/5x−7/3 | | 2y+16=6y | | 2x(x^2-4x+3)=0 | | 135=lwh | | 15n=-45 | | 3x^2sin(3x)=0 | | 2y+8=3y-4 | | x(3-x)=-4 | | -7(-6x+5)=-7x+14 | | -n/5=8 |